Morphological variation of mountain blackeye (Chlorocharis emiliae) populations in Malaysian Borneo - Ramji, M.F.S; Rahman, M.A; Tuen, A.A. (Penerbit Universiti Kebangsaan Malaysia, 2012)
The mountain blackeye (Chlorocharis emiliae) is one of the few Bornean endemic birds which presents an excellent model species to illustrate evolution and speciation. Here, we use discriminant function analysis to elucidate the morphological variation on 40 specimens of mountain blackeye from four populations namely Mount Kinabalu, Mount Trus Madi, Mount Murud and Mount Mulu. The test successfully distinguished all four populations accordingly by respective nominated subspecies. Tarsus length and bill length were identified as the best predictors from nine character loadings observed which also included bill depth, bill width, head bill, wing length, wing span, tail length and total length. Along with this, the morphological patterns also revealed that solid skeletal characters such as bill length, bill depth, bill width and tarsus are genuine predictors of morphological variation and body size within species as compared to feather-based characters. The evolution of such morphological traits is more pronounced due to different ecological adaptation of the mountain blackeye populations. Several factors such as phenotypic plasticity, foraging behaviours and food availability may have influenced the morphological variation between the subspecies.